DAMPAK PENGGUNAAN BAHASA GAUL DI KALANGAN REMAJA TERHADAP BAHASA INDONESIA - Gusnayetti, Gusnayetti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
In sociolinguistic studies, language is defined as a symbol system, in the form of sound, arbitrary, productive, dynamic, diverse and human. Understanding of language in the big Indonesian dictionary, understanding language in general can be defined as a symbol, and understanding language according to the term is a communication tool in the form of a system of symbols produced by speech organs in humans. Language is also part of culture and it is language that develops culture as we know it today. Language can also act as a tool for social integration as well as a tool for social adaptation, considering that Indonesian has a pluralistic language. Slang is the typical language of teenagers (words that are changed in such a way that it can only be understood between them) can be understood by almost all teenagers in the country who are reached by the mass media. Yet the terms are evolving, changing and increasing almost every day. Slang is a language that has unique terms, while the second definition is made clear again that it is teenagers who use the language and the language will continue to develop. As for the characteristics of slang, the factors that support the prevalence of slang among teenagers, the influence of slang on Indonesian and the impact of the use of slang.